Can differences between continental and insular habitats influence the parasites communities associated with the endemic frog Haddadus binotatus ? - Aguiar, A. [UNESP]; Morais, D. H.; Yamada, F. H.; Dos Anjos, L. A. [UNESP]; Da Silva, L. A.F. [UNESP]; Da Silva, R. J. [UNESP] (Cambridge University Press (CUP), 2020)
Habitats characterized by geographic isolation such as islands have been studied using different organisms as models for understanding the dynamic and insular patterns of biodiversity. Determinants of parasite richness in insular host populations have been conducted mainly with mammals and birds, showing that parasite richness decreases in insular areas. In the present study, we predicted that the type of environment (insular or continental) can influence the richness, diversity and abundance of parasites associated with the endemic frog Haddadus binotatus (Spix, 1824). We sampled frogs in two insular and two mainland fragments to survey their helminth parasites. The total richness was composed of 15 taxa of Nematoda and two of Acanthocephala, and the community composition of the two islands had more similarities between them than the two mainland localities. The insular effect was positive for richness and abundance of helminths, and no significant effect was observed on helminth diversity - even the mean diversity presented high numbers for the islands. We presumed that insular hosts could have lost some parasites in the colonization process when these continental islands were separated from the mainland, approximately 11,000 years ago. However, the high richness and abundance on islands can be explained by an epidemiological argument, which considers high population density due to insularity and other features of the host as factors that increase parasite transmission success among individuals.
Keywords: Atlantic Forest; diversity; leaf-litter frog; Metazoan parasites